2016
DOI: 10.1080/02791072.2015.1130279
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Approach to the Heavy Cannabis User in the Age of Medical Marijuana

Abstract: This article begins with a case vignette exemplifying the common clinical problem of heavy marijuana users. The epidemiology and basic science underlying cannabis dependence is outlined, followed by clinical strategies for basing a therapeutic alliance on known research findings and using motivational interviewing to deal with typical patterns of denial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…At the same time, counselors saw the potential harm of cannabis use and opted to use less directive approaches, such as motivational interviewing and psychoeducation, to raise awareness among clients about the risks associated with marijuana use. These findings are consistent with Cermak (2016), who suggested the importance of developing a nonconfrontational therapeutic alliance with clients who use recreational marijuana, as well as using motivational interviewing and psychoeducation to raise awareness among clients about the downsides of frequent marijuana use.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At the same time, counselors saw the potential harm of cannabis use and opted to use less directive approaches, such as motivational interviewing and psychoeducation, to raise awareness among clients about the risks associated with marijuana use. These findings are consistent with Cermak (2016), who suggested the importance of developing a nonconfrontational therapeutic alliance with clients who use recreational marijuana, as well as using motivational interviewing and psychoeducation to raise awareness among clients about the downsides of frequent marijuana use.…”
Section: Discussionsupporting
confidence: 89%
“…The majority of participants in our study identified harm reduction and motivational enhancement strategies as useful in responding to changing marijuana laws. This approach is consistent with the literature (Brooks et al, 2017;Cermak, 2016), and counselors should assess whether the substance is problematic (i.e., Does an individual meet the criteria for cannabis use disorder?) and make considerations regarding a client's use of other substances.…”
Section: Implications For Counselingmentioning
confidence: 59%
“…Coded categories were not mutually exclusive such that a reference might have defined the principle of patient-centered care at more than one category. Bracketed numbers represent the number of unique references coded at each category b References coded at this category [45, 48, 51, 57, 59, 6166, 71, 76, 77, 79, 83, 89, 91, 93, 94, 96, 99, 103, 104, 118128] c References coded at this category [41, 43, 45, 48, 51, 57, 61, 6366, 71, 74, 8991, 96, 103, 118–121, 123, 125132]…”
Section: Resultsmentioning
confidence: 99%
“…b References coded at this category [45, 48, 51, 57, 59, 6166, 71, 76, 77, 79, 83, 89, 91, 93, 94, 96, 99, 103, 104, 118128]…”
Section: Resultsmentioning
confidence: 99%